Los trastornos de la conducta alimentaria: ¿menos es más? - Teresa Díez Fernández; Carmen Yegler Velasco; Francisca Casas Martínez; José Ángel Gómez Carrasco; Jorge Luis Gómez González (Universidad de Alicante, 2012)
We have wondered if the disorders of the alimentary conduct (DAC) are an exclusive and recent phenomenon of the Western societies, produced or encouraged by the mass media (MM) and, if it is so, who they could have been the changes experienced in the ethical values of our societies that have encouraged the peak of these pathologies along the 20th century. We concluded that conducts similar to what we today identified like DAC (anorexia nervosa and/or bulimia), they have existed from the antiquity. Probably from the incorporation of the Christianity to the history of the Western civilization, previous influence of this of eastern religious values that established a separation body-soul or matter-spirit. In cultures with their views are far apart from the Westerner, the DAC they virtually have not existed and they only appear after the incorporation of the ethical values of the occident developed to the same. The MM influences mightily in the experience of the own image that has the people, particularly the women. The universality of the prototype of high and thin woman, it lead to a distortion of the own corporal image that predisposes to the mental disorder. The change of what it traditionally was considered wealth and social value happened to end of the 19th century and beginnings of the 20th century, next to the incorporation of women into the workforce in the cities, they coincide step to step with what, concerning the aesthetics, it occurred in calling the modern style and that of the new woman; "less is more" it is the leitmotiv. Anorexia nervosa and bulimia are logical consequence of the prevaling norm.